Assignment-Based Balaghah Learning Module Application to Increase Literary Appreciation - Nurul Musyafa’ah (Syntax Corporation Indonesia, 2021)
Literary appreciation is the real goal in learning Balaghah. So we need a balaghah learning module that can harmonize balaghah learning with the real goal, namely the appreciation of literature. This research is intended to: 1) reveal the steps of making assignment-based Balaghah learning modules to improve Literary Appreciation; 2) Measure the effectiveness of using assignment-based Balaghah learning modules as an effort to increase literary appreciation. The researcher uses a qualitative and quantitative approach with the design of the Borg and Gall R&D research method which is simplified into six steps, namely: needs analysis, design of teaching materials, validity from experts, revisions, field tests, and refinement of modules as textbooks. The data collection methods used by researchers are observation, interviews, questionnaires, tests, and documentation studies. The results of this study: 1) The realization of the Balaghah learning module along with its characteristics and advantages, namely a module that can increase assignment-based literary appreciation in the learning process so that students can communicate and apply Arabic language skills with beautiful language and literary styles. 2) The Balaghah learning module developed is proven to be effective in increasing literary appreciation, based on the conclusion that the t-test with a level of 9,000 is greater than t-table 2.101 and a significance value of 0.000 is less than alpha of 0.050, from this it shows that there is a clear difference after the application assignment-based Balaghah Science Learning module to increase literary appreciation at the Adnan Al-Charis Islamic Boarding School Bojonegoro